Patogenisitas Virus Tungro pada Varietas Tetua Padi Tahan Tungro - R Heru Praptana; Y B Sumardiyono; Y Andi Trisyono (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2013)
Tungro is one of the major diseases in rice which has become a constraint in increasing rice production in Indonesia. Tungro is caused by infection of two different viruses, i.e. Rice tungro bacilliform virus (RTBV) and Rice tungro spherical virus (RTSV), both of which can only be transmitted by green leafhoppers Nephotettix virescens (Distant) in a semipersistent manner. Since there is an indication of the existance of virulence variation of tungro viruses from different areas and the specific relationship between resistance of varieties and tungro viruses isolates, it is important to study the pathogenicity of tungro viruses from some endemic areas in Indonesia. This study aimed to identify the pathogenicity of tungro viruses from several endemic areas in Indonesia in some resistant varieties. One susceptible variety i.e. TN1 and ten resistant varieties were used in the study. Surveys and collection of infected plants and green leafhoppers were done in tungro endemic areas, namely West Java, Central Java, Yogyakarta, Central Sulawesi, West Sulawesi, South Sulawesi, Bali and West Nusa Tenggara. Artificial transmission using the test tube method was used in the pathogenicity test. Green leafhoppers caught from the field were used as transmitters.. The pathogenicity of tungro viruses were identified by the values of the incidence of tungro and the diseases indexes (DI). The result showed that difference in pathogenicity of tungro viruses in some resistant varieties was observed. Isolates from Central Java, Central Sulawesi and West Nusa Tenggara were able to infect all of resistant varieties and the pathogenicity of Central Java isolate was the highest among the other isolates.